Karakteristik Edible Film Aktif Berbasis Kitosan dengan Penambahan Ekstrak Daun Jati - Prima Dewi Ramadhani; Supriyadi Supriyadi; Henny Krissetiana Hendrasty; Eriva Meytara Budi Laksana; Umar Santoso (Jurnal Teknologi dan Industri Pangan, 2023)
Teak tree (Tectona grandis) is a tropical tree whose wood is often used in the furniture industry, while the leaves are still underutilized. Teak leaves possess active compounds with potential to be further explored. On the other hand, currently biodegradable-based packaging is being developed to address environmental problems. For this reason, research was carried out on active edible film made from chitosan with addition of active ingredients from teak leaf extract. This study investigated the physical characteristics (color, tensile strength, elongation, solubility, cell microstructure, water vapor transmission rate) and chemical characteristics (moisture content, functional groups, antioxidant and antimicrobial activity) of active edible film made from chitosan with addition of teak leaf extract. The research consisted of three stages. The first stage included the extraction of teak leaf using ethanol and evaluation of its antioxidant and antimicrobial activity. The second stage comprised edible film preparation from chitosan at 1 and 1.5% concentrations, and teak leaf extract addition at 0, 0.1, 0.2% concentrations. The third stage was the characterization of active edible film for physical and chemical properties. The results showed that teak leaf extract had antioxidant activity as evaluated by DPPH method with IC50 value of 46.78 ppm. The teak leave extract also showed antibacterial activity on Staphylococcus aureus. The optimum condition for the production of active edible film was use of 1% chitosan and 0.2% teak leaf extract. The active edible film produced had antioxidant activity of 8.53% RSA, 30.16%, moisture content, 38.28% solubility,1.52 MPa tensile strength, 9.54% elongation, water vapor transmission rate of 3672.32 g/m2, but the film did not show inhibitory effects on S. aureus.